Fatigue behavior of Zircaloy-2 under asymmetric loading at 400°C - Rajpurohit R.S.; Srinivas N.C.S.; Singh S.R.; Singh V. (My University, 2025)
Nuclear core components such as cladding tubes of Zircaloys often exhibit progressive extension with number of cycles under asymmetric cyclic loading with tensile mean stress and undergo premature failure against the life stipulated under symmetric loading. The accumulation of plastic strain depends on the applied mean stress, stress amplitude, stress rate and service temperature. In the present investigation accumulation of plastic strain in the Zircaloy-2 and its fatigue life is studied under different combinations of the mean stress from 45 to 70 MPa, stress amplitude from 95 to 120 MPa and stress rate from 30 to 750 MPa/s, at 400°C. While there is decrease in fatigue life with increase in the mean stress and stress amplitude, fatigue life is increased with rise in stress rate from 100 MPa/s and above. The increase in fatigue life above the stress rate of 150 MPa/s, at 750 MPa/s, is due to decrease in the effective cumulative plastic strain. Fatigue life is increased also below the stress rate of 100 MPa/s, at stress rate 30 MPa/s, but due to the effect of dynamic strain aging in this alloy at 400°C. There is also significant effect of the test variables on fracture behavior and the deformed microstructure. © 2017